Der Kirchberg von Deutschfeistritz, Bezirk Graz-Umgebung,Steiermark - eine frühmittelalterliche Burgstelle? - Gutjahr, Christoph (Arheološki vestnik, 2006)
In 1949, the Styrian Landesmuseum Joanneum carried outarchaeological excavations at Kirchberg in Deutschfeistritz(Deutschfeistritz district, Graz county), located approximate-ly 20 km north of Graz at the juncture of the Übelbach andMur valleys. This resulted in the most extensive finds to thepresent from an early medieval settlement in Styria. An im-portant route ran along the Übelbach valley with a pass acrossGleinalp in the upper valley of the Mur River, and this wasquite important in the early Middle Ages as well. The articlepublishes the finds from the earlier excavations and brieflyindicates their great significance for the early medieval periodin Styria. It is possible to conclude on the basis of the docu-mentation that they excavated a structure that was suggestedto have contained five rooms. Several hearths and finds of ironslag indicate that this was an area where iron was forged. Mostof the pottery fragments belong to the 8th-11th centuries, withan emphasis on the 9th century. Fragments of loom weightswere also found, along with two spindle-whorls, knives withtanged handles, bone tools (awl, needle), an iron key, a spurwith platelets and rivets (8th century), whetstones, iron slag,and two undistinguishable bronze objects. Given the presenceof the only as yet known early medieval blacksmith ́s work-shop in Styria and the corresponding finds, it is very likelythat the seat of an estate (a central castle) was originally lo-cated at Kirchberg in Deutschfeistritz.